HEXAGONAL RESTARTING AUTOMATA - P, ANITHA; Dersanambika, Dr. K.S. (Journal of Global Research in Mathematical Archives(JGRMA), 2017)
This paper focuses on a model of automaton for hexagonal pictures with particular attention given to scanning strategies.In this restarting automaton the picture is being scanned at each step and interpreted.We point out here only a particular scanning strategy.